Pandemic-related racial discrimination and its health impact among non-Indigenous racially minoritized peoples in high-income contexts: a systematic review. (1st October 2021) - Yashadhana, Aryati; Derbas, Alexia; Biles, Jessica; Grant, Julian
Summary: This study aims to review articles reporting the perspectives and experiences of pandemic-related discrimination among racially minoritized peoples in high-income contexts. We searched online databases (Medline, EMBASE, PsycINFO, Web of Science, and ProQuest) for peer-reviewed articles published between January 2002 and October 2020. Eligible studies reported either quantitative or qualitative accounts of pandemic-related discrimination from the perspectives of racially minoritized peoples in high-income contexts. Two authors screened 30% of titles/abstracts, and all full-text articles. Each article included for extraction underwent a quality assessment by two reviewers. Data were extracted and categorized thematically using NVivo 12, followed by a secondary analysis informed by critical race theory. Of the 1289 articles screened, 16 articles from five countries met the inclusion criteria. Racial discrimination is heightened during pandemic periods, due to the social association of specific racial groups with pandemic diseases including COVID-19, SARS (Asian), H1N1 (Hispanic) and Ebola (African). Fear based responses to racially minoritized peoples during pandemic periods included verbal/physical abuse, hypersurveillance, and avoidance, often occurring in public spaces. Pandemic-related racism had subsequent impacts on mental health and health care accessibility. Various coping strategies, including community support, avoidance, and problem solving, were documented in response to racial discrimination. Racialized discrimination and violence is a serious threat to the health and wellbeing of racially minoritized peoples, particularly due to its increase during pandemic periods. Racism must be recognized as a public health issue, and efforts to address its increased impact in pandemic contexts should be made, including ensuring that adequate representation of racially minoritized groups is present in policy, planning, and implementation.